Analysis of the modern state of legal adjusting of financial monitoring - Білько, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In the article examined features of the legal adjusting of realization of the financial monitoring and his belongingto science of financial right.